2016
DOI: 10.1682/jrrd.2015.07.0145
|View full text |Cite
|
Sign up to set email alerts
|

Elevated vacuum suspension preserves residual-limb skin health in people with lower-limb amputation: Randomized clinical trial

Abstract: Abstract-A growing number of clinical trials and case reports support qualitative claims that use of an elevated vacuum suspension (EVS) prosthesis improves residual-limb health on the basis of self-reported questionnaires, clinical outcomes scales, and wound closure studies. Here, we report first efforts to quantitatively assess residual-limb circulation in response to EVS. Residual-limb skin health and perfusion of people with lower-limb amputation (N = 10) were assessed during a randomized crossover study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…4 The study did not account for movement at the interface, mostly because there was not a method to quantify these data at the time of the study. The traditional teaching from Orthotic and Prosthetic educational programs is that motion should be eliminated between the residual limb and socket, although this is generally determined by visually inspecting the socket as the user ambulates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The study did not account for movement at the interface, mostly because there was not a method to quantify these data at the time of the study. The traditional teaching from Orthotic and Prosthetic educational programs is that motion should be eliminated between the residual limb and socket, although this is generally determined by visually inspecting the socket as the user ambulates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if a relatively similar level of suspension is generated at a lower vacuum setting, is there a need to draw the highest possible vacuum pressure of the pump? How did differences in vacuum pressure setting, and therefore amount of motion between the limb and socket, impact the results of the previous limb health study 4 ? Should all motion totally be eliminated, or is there a threshold of movement that is optimal for the health of the limb and/or user comfort?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] We recently reported on the beneficial effects of elevated vacuum suspension as they relate to residual limb health in TT and TF subjects. 21 In light of the small sample size employed in the current study, outcomes were not stratified according to suspension type. Future efforts will be focused to investigate the relationship between suspension type and residual limb skin health.…”
Section: Discussionmentioning
confidence: 99%
“…The LimbLogic Ā® vacuum system developed as a result of a Veterans Affairs (VA) grant funded collaborative work with Ohio Willow Wood was commercialized for clinically relevant quantification of prosthetic socket performance. Elevated vacuum suspension (EVS) [20,21] (Figure 3) creates subatmospheric pressure between the prosthetic socket and liner worn over the residual limb. Studies performed with this system identified that variances among individuals may be a result of different gait styles, tissue types, residual limb geometries, prosthesis weight distribution, and socket fit.…”
Section: The Socket/limb Interfacementioning
confidence: 99%